2015
DOI: 10.1007/s11127-015-0250-2
|View full text |Cite
|
Sign up to set email alerts
|

Partial fiscal decentralization and sub-national government fiscal discipline: empirical evidence from OECD countries

Abstract: Recent theoretical research suggests that financing sub-national governments' expenditure out of own revenue sources is linked to more responsible budgeting, because the financial implications of spending decisions then are internalized within a jurisdiction. We test this proposition empirically on a sample of 23 OECD countries over the 1975-2000 period, and find evidence in line with the hypothesis that greater revenue decentralization (measured as sub-national governments' share of own source tax revenues in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 25 publications
2
38
0
1
Order By: Relevance
“…However, this study also finds that expenditure decentralization has a negative impact on regional economic growth, but level of significance is weak. These findings align with the empirical evidence from the studies of fiscal decentralization and economic growth in OECD economies by Asatryan, Feld, & Geys (2015) and Blochliger and Akgun (2018), both of whom described that decentralization of tax revenues tends to have a stronger impact than spending decentralization and such evidence is more likely to occur in a smaller government. While intergovernmental transfers appeared to be associated with slower growth, both studies found that balanced decentralization is conducive to growth.…”
Section: Resultssupporting
confidence: 88%
“…However, this study also finds that expenditure decentralization has a negative impact on regional economic growth, but level of significance is weak. These findings align with the empirical evidence from the studies of fiscal decentralization and economic growth in OECD economies by Asatryan, Feld, & Geys (2015) and Blochliger and Akgun (2018), both of whom described that decentralization of tax revenues tends to have a stronger impact than spending decentralization and such evidence is more likely to occur in a smaller government. While intergovernmental transfers appeared to be associated with slower growth, both studies found that balanced decentralization is conducive to growth.…”
Section: Resultssupporting
confidence: 88%
“…In the wake of the 2008-2009 fi nancial crisis, more attention was also paid to the infl uence of local fi nances on the rising defi cits of general government sectors. A recent study confi rmed that greater fi scal autonomy involves stricter budgetary discipline (Asatryan et al, 2015).…”
Section: Post-crisis Trends In Researchmentioning
confidence: 99%
“…On the other hand Asatryan at al. [13] found that that greater tax (revenue) decentralization is associated as well with improved sub-national government budget deficits/surpluses.…”
Section: (3) the Degree Of Fiscal Decentralizationmentioning
confidence: 99%